Predictive Maintenance and Reliability Modeling of Rural Broadband Networks: A Condition-Based Study of BharatNet Infrastructure (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores the operational status and reliability of rural broadband infrastructure in 113 Gram Panchayats (GPs) in the Puducherry district, focusing on critical assets such as Optical Network Terminals (ONT), Central Control Units (CCU), battery systems, and solar panels, using a condition-based performance evaluation. Results from data analysis in SPSS show that 87.6% of GPs are operational (\"UP\"), but technical issues, including high fault rates in earthing and solar systems, are still prevalent, highlighting the need for predictive maintenance and real-time monitoring to ensure uninterrupted rural connectivity in support of India's digital empowerment objectives.